The experiences of newly qualified nurses regarding support systems during transition into a general nurse position at a Nelson Mandela Bay Metropolitan private hospital - Ingram, Priscilla Valencia (Stellenbosch : Stellenbosch University, 2026)
Thesis (MNur)--Stellenbosch University, 2026.